2002
DOI: 10.1590/s1415-47572002000100014
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing electroporation-mediated gene transfer to Stylosanthes guianensis (Aubl.) Sw. protoplasts

Abstract: In order to develop a high-efficiency and reproducible transformation protocol for Stylosanthes guianensis we assessed the biological and physical parameters affecting plant electroporation protoplasts. Energy input, as combinations of electric field strengths discharged by different capacitors, electroporation buffer and DNA form were evaluated. Transformation efficiency was assayed in vivo as transient reporter gene expression, using the GFP-coding gene mgfp5 driven by a CaMV 35S constitutive promoter. Energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
1
8
0
1
Order By: Relevance
“…Gene electrotransfer of plant protoplasts was successfully applied for transformation of several crop species such as maize, rice, wheat, sorghum, soybean, and rye (Fromm et al 1986;Lee et al 1986;Christou et al 1987;Pitt et al 1997;Quecini et al 2002). Cell viability preservation is crucial for production of transgenic plants, as transformed protoplast should maintain the ability of normal organogenesis.…”
Section: Plant Protoplast Electroporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene electrotransfer of plant protoplasts was successfully applied for transformation of several crop species such as maize, rice, wheat, sorghum, soybean, and rye (Fromm et al 1986;Lee et al 1986;Christou et al 1987;Pitt et al 1997;Quecini et al 2002). Cell viability preservation is crucial for production of transgenic plants, as transformed protoplast should maintain the ability of normal organogenesis.…”
Section: Plant Protoplast Electroporationmentioning
confidence: 99%
“…Conflicting reports about electrotransfected plant protoplast regeneration ability are found in the literature. Some authors reported increased cell division, plant regeneration, and DNA synthesis in protoplast transformed by electroporation (Rech et al 1987;Rech et al 1988;Chand et al 1988;Ochatt et al 1988;Joersbo et al 1991), while others found slower plant regeneration of electrotransfected protoplasts (Quecini et al 2002). In some studies, increasing electric filed strength and the number of pulses decreased plant protoplast viability and plating efficiency.…”
Section: Plant Protoplast Electroporationmentioning
confidence: 99%
“…As variedades de S. guianensis, apresentam ampla variabilidade relacionada a características de produção, adaptação a solos ácidos e de baixa fertilidade, tolerân-cia à seca e tolerância a pragas e doenças sendo consideradas moderadamente tolerantes à salinidade (Gonzalez et al, 2000;Quecini et al, 2002).…”
Section: Enzymatic Reaction To Saline Stress During Stylosanthes Germunclassified
“…In Stylosanthes guianensis, a tropical forage legume, direct DNA uptake using an electroporation-mediated method (3.2 x 10 7 electroporated protoplasts produced 50 regenerants, from which 18 were transgenic) was superior to a biolistic approach (Quecini, 1999;Quecini et al, 2002). The protocol described herein could be used for genetic transformation of alfalfa, and somatic hybridization experiments involving Medicago species.…”
Section: In Vitro Proceduresmentioning
confidence: 99%
“…Therefore the protocol of Atanassov & Brown (1984) was used to obtain somatic embryos and, subsequently, plants from M. sativa 'Rangelander' protoplasts. This system should allow microparticle bombardment and protoplast electroporation, the principal mechanisms for direct gene delivery into legume plant cells (Aragão et al, 1999;Potrykus, 1991;Quecini et al, 2002). Genetic engineering methods are very useful for the transference of disease resistance genes into alfalfa genome in Brazil, namely to control the fungi Rhizoctonia solani and Colletotrichum trifolii.…”
Section: Introductionmentioning
confidence: 99%